Impact of VR technology in physics teaching on students’ knowledge: a study on body acceleration - Kurbanbekov, Bakitzhan; Ramankulov, Sherzod; Nurizinova, Makpal; Asanbek, Beksultan (Institute of Advanced Engineering and Science, 2025)
The integration of virtual reality (VR) technology into education represents a promising innovation, particularly in enhancing the effectiveness of physics teaching. Traditional physics instruction often lacks interactive and immersive elements, which can limit students’ understanding of complex physical phenomena. This study addresses the challenge of improving comprehension of body acceleration by incorporating VR-based laboratory simulations. A quasi-experimental design was implemented, involving 222 university students randomly assigned to control and experimental groups. The experimental group conducted virtual experiments using VR simulations developed with Blender and Unity software, while the control group engaged in traditional lab activities. Data were collected through pre- and post-tests and analyzed using independent t-tests and G*Power software to assess statistical significance. The results revealed a notable improvement in learning outcomes for students exposed to VR-enhanced instruction, demonstrating increased engagement, deeper conceptual understanding, and improved ability to connect theoretical knowledge with practical application. This study confirms that VR technology is a powerful tool for modernizing science, technology, engineering, and mathematics (STEM) education and holds significant potential for improving cognitive outcomes and student motivation in scientific learning environments.